Neighbor-based dynamic connectivity factor routing protocol for Mobile Ad hoc Network - Ejmaa, Ali Mohamed E.; Subramaniam, Shamala; Ahmad Zukarnain, Zuriati; Mohd Hanapi, Zurina (Institute of Electrical and Electronics Engineers, 2016)
Recently, Mobile Ad hoc Networks (MANETs) have witnessed rapid development due to the low cost, diversity, and simplicity of mobile devices. Such devices can form a reliable network in a short time for use as a rescue information system after a natural disaster, where the communication infrastructure may no longer be available or accessible. Because the nodes in such a network are free to move at any time in the absence of centralized control, routing is considered to be the most challenging issue. Moreover, some routing protocols, such as Neighbor Coverage-Based Probabilistic Rebroadcast (NCPR), completely rely on preset variables, which are required to be set by the system administrator based on the scenario. Unfortunately, the setting that is proper for a specific scenario is not suitable for another scenario. In addition, some other routing protocols, such as Ad hoc On-demand Distance Vector (AODV), employ the Route REQuest message (RREQ) flooding scheme to find a path to a particular destination in the route discovery stage. Although the flooding scheme guarantees better reachability, it introduces undesirable routing overhead, which in turn leads to system performance degradation. Thus, this paper proposes a novel routing protocol, neighbor-based Dynamic Connectivity Factor routing Protocol (DCFP), that is able to dynamically probe the status of the underlying network without the intervention of a system administrator based on a novel connectivity metric, while reducing the RREQ overhead using a new connectivity factor. Furthermore, extensive simulation experiments are conducted to evaluate the performance of the proposed DCFP, where the NCPR and AODV are used as a benchmark. The proposed DCFP manages to address the need for preset variables in NCPR. Simulation results show that DCFP outperforms both NCPR and AODV in terms of end-to-end delay, normalized routing overhead, MAC collision, energy consumption, network connectivity, and packet delivery ratio due to its novel mechanism for reducing redundant RREQ.